Revealing the Therapeutic Uses of Garlic (Allium sativum) and Its Potential for Drug Discovery. (30th December 2021) - Tesfaye, Azene
Abstract : Background . Garlic is a common bulb vegetable that is used to flavor and flavor food. The plant contains biologically active components that contribute to its pharmacological properties. This paper attempts to examine the therapeutic uses and potential role in the drug development of garlic for various human diseases. Methods . To obtain crucial data and scientific knowledge about the therapeutic uses of garlic, systematic literature searches were conducted using key terms on well-known indexed platforms such as PubMed, Scopus, Web of Science, Medline, Embase, and popular search engines. Results . Garlic, which is utilized as a spice and flavoring ingredient, is found to have fundamental nutritional components. Carbohydrates, protein, fat, minerals, water, and vitamins are all found in abundance in this plant. The plant also has a high medicinal value and is used to cure a variety of human diseases. It has anti-inflammatory, rheumatological, ulcer inhibiting, anticholinergic, analgesic, antimicrobial, antistress, antidiabetes, anticancer, liver protection, anthelmintics, antioxidants, antifungal, and wound healing properties, as well as properties that help with asthma, arthritis, chronic fever, tuberculosis, runny nose, malaria, leprosy, skin discoloration, and itching, indigestion, colic, enlarged spleen, hemorrhoids, fistula, bone fracture, gout, urinary tract disease, diabetes, kidney stones, anemia, jaundice, epilepsy, cataract, and night blindness. Conclusions . The nutritional content of the plant is significant, and it has incredible therapeutic potential. The findings of this study are needed to investigate the therapeutic potential, as it may be a promising option for drug development.